A review of the incidence of head injuries in football, baseball, ice hockey, and cycling - Shaw, J. A.; Nielsen, B. (American Journal of Sports Science, 2019)
Head injuries in sports have merited greater attention from professionals, the media, and the general public in recent years. The purpose of this research was to conduct a review of articles that focus on the incidence of head injuries in football, baseball, ice hockey, and cycling. Twenty three studies were identified for inclusion because they contained quantitative data on the number or percentage of head injuries in those four sports. A table was created comparing the data by: sport, research design, level of play, and number of head injuries. Analysis of the data showed that the most studied sport was ice hockey, the most studied level of play was the professional level, and the most used study designs were case studies and emergency department surveillance. Some studies included implementation of prevention strategies to decrease the incidence of head injuries. The most common prevention strategies were rule changes and better equipment. Future studies will help determine the most successful prevention strategies that can be implemented in each sport to further reduce the incidence of head injury in sports.